Is faecal microbiota transplantation an option to eradicate highly drug-resistant enteric bacteria carriage?. Issue 4 (April 2017) - Davido, B.; Batista, R.; Michelon, H.; Lepainteur, M.; Bouchand, F.; Lepeule, R.; Salomon, J.; Vittecoq, D.; Duran, C.; Escaut, L.; Sobhani, I.; Paul, M.; et al.
Summary: Carbapenem-resistant Enterobacteriaceae (CRE) or vancomycin-resistant enterococci (VRE) carriage present a major public health challenge. Decolonization strategies are lacking. We aimed to evaluate the impact of faecal microbiota transplantation (FMT) on a cohort of patients with digestive tract colonization by CRE or VRE. Eight patients were included: six carrying CRE and two colonized by VRE. One month after FMT, two patients were free from CRE carriage, and another patient was free from VRE after three months. In our experience, this strategy is safe.